THEORY OF DIDACTIC PRINCIPLES IN MATHEMATICS LESSONS - Sunnatulla Dostov; Khushbakova Saodat Kochkor's daughter; Boymatov is the son of Islam Kholmakhmat (Journals Park Publishing, 2022)
In this article, the theory of didactic principles in mathematics lessons, the issue of using other subjects in mathematics lessons, clearly showing in the program, some educational situations of aspects of computer convenience in teaching mathematics, the correct choice of didactic games in preparing for the lesson described in detail.
Keywords: didactic principles, didactic games, computer usability, theory of principles, active thinking.